Search for supersymmetry with a compressed mass spectrum in the vector boson fusion topology with 1-lepton and 0-lepton final states in proton-proton collisions at √s = 13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Verlag, 2019)
A search for supersymmetric particles produced in the vector boson fusion topology in proton-proton collisions is presented. The search targets final states with one or zero leptons, large missing transverse momentum, and two jets with a large separation in rapidity. The data sample corresponds to an integrated luminosity of 35.9 fb−1 of protonproton collisions at √ s = 13 TeV collected in 2016 with the CMS detector at the LHC. The observed dijet invariant mass and lepton-neutrino transverse mass spectra are found to be consistent with the standard model predictions. Upper limits are set on the cross sections for chargino ( ˜χ ± 1 ) and neutralino ( ˜χ 0 2 ) production with two associated jets. For a compressed mass spectrum scenario in which the ˜χ ± 1 and ˜χ 0 2 decays proceed via a light slepton and the mass difference between the lightest neutralino ˜χ 0 1 and the mass-degenerate particles ˜χ ± 1 and ˜χ 0 2 is 1 (30) GeV, the most stringent lower limit to date of 112 (215) GeV is set on the mass of these latter two particles.